До питання про соціальне районування Ольвії елліністичного часу - Лейпунська, Н.О. (Археологія, 1997)
У статті йдеться про порівняння особливостей планування, будівництва та речового матеріалу двох районів Ольвії та різниці в соціальному статусі їх мешканців. Статья посвящена сравнению двух участков раскопок Ольвии — Центрального квартала и участка НГС. Первый раскоп находится в центре Верхнего города, второй — в северной части Нижнего. Анализ характера планировки, особенностей домостроительства и декора помещений, статистические оценки вещевого материала позволили предположить разный социально-экономический статус жителей двух районов Ольвии. Население Центрального квартала принадлежало верхушке ольвийской общины, жители участка НГС — ее среднему слою. The paper is devoted to comparison of two plots of excavation trench in Olbia — the Central block and NGS. The first trench is in the centre of the Upper town, the second — in the northern part of the Lower town. The analysis of the project, peculiarities of house-building and decoration of the interior, statistical estimation of material findings have permitted supposing that inhabitants of these two districts in Olbia have different socio-economic status. People who lived in the central block were the cream of the Olbian community, while inhabitants of the NGS block belonged to the middle layer.